Low Latency Audio Video: Potentials for Collaborative Music Making Through Distance Learning. (June 2016) - Riley, Holly; MacLeod, Rebecca B.; Libera, Matthew
The primary purpose of this study was to examine the potential of LOw LAtency (LOLA), a low latency audio visual technology designed to allow simultaneous music performance, as a distance learning tool for musical styles in which synchronous playing is an integral aspect of the learning process (e.g., jazz, folk styles). The secondary purpose was to describe participant perceptions of the effectiveness of three technologies used to teach music: LOLA, PolyCom, and Skype. To achieve these goals, we isolated a classical masterclass, jazz lesson, and old-time fiddle session and described trends for these lessons across the three technology platforms. Participants rated the overall effectiveness of LOLA ( M = 4.25) higher than PolyCom ( M = 3.06) and Skype ( M = 2.80). Participants shared their perception that LOLA was superior to other technologies for learning and teaching music. Implications for music teaching are discussed.